GOVERNMENT INVOLVEMENT IN SPORT FOR ALL, ELITE SPORT AND IT RELATION TO LEISURE POLICY - Aman Mohd Salleh (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2015)
The ‘sport ’ in Sport for All is loose term for such disparate activities as informal recreation, leisure pursuits, play, health promotion activities as well as formal organised sport. Elite sport refers to power and performance sport and includes all those that are highly organised and competitive. Neither Sport for All, nor elite sport, is the substitute for a nation public leisure policy. Governments may have grounded their policies in very different legitimations, which may generate subtle yet telling differences in policy implementation. Leisure policy should not be on the number of gold medals our competitors can win, but rather on the inspiration and impetus their success gives to the citizens of our nation for mass participation in physical activity in all age groups and at all levels of ability.